Doctrinal Orthodoxy, Salience, and the Consequential Dimension - Gibbs, David R. (Journal for the scientific study of religion, 1973)
Using symbolic interactionist theory to derive the basic proposition that an empirical relationship between the creedal and consequential dimensions of religiosity should appear only to the extent to which one's relgious identity is salient, we examined a sample of Protestant church members in Indianapolis (N = 604). A relationship appeared only for those dependent variables in which the organized church was directly implicated, and even then only in the very highest salience category. With the proviso that a very high level of salience is required to produce a relationship, all of the other studies of the relationship of religious orthodoxy to political attitudes and behavior fall neatly into place. Evidence is also presented which indicates that the theory predicts behavior at the extremes of the creedal continuum, making separate theories of religious and political extremism unnecessary.